Control and treatment of landfill leachate for sanitary waste disposal - Aziz, Hamidi Abdul, 1965- (Hershey : Information Science Reference, 2016)
'This book presents research-based insights and solutions for the proper management and treatment of landfill leachate, highlighting relevant topics on emerging technologies and treatment innovations for minimizing the environmental hazards of waste disposal'--
Includes bibliographical references and index.
Keywords: Refuse and refuse disposal; Fills (Earthwork).